Profile of alanine aminotransferase and hepatic iron accumulation in thalassemic patients with or without anti-hepatitis C virus - Purnamawati S P; Pamela Kartoyo; Imral Chair; Julfina Bisanto; Hanifah Oswari (Indonesian Pediatric Society, 2004)
Background Repeated blood transfusions in thalassemic patientscause iron accumulation in tissues and might impair organ func-tion. Other peril of blood transfusion is hepatitis C virus infection.Objectives This study aimed to find out the proportion of increasedalanine aminotransferase (ALT), increased transferrin saturation(TS), and positive anti hepatitis C virus (anti-HCV) among thalas-semic patients and to get the profile of ALT among thalassemicpatients who have increased TS and positive anti-HCV.Methods This cross-sectional descriptive study was conductedon β- and β-HbE-thalassemic patients at the Thalassemia Outpa-tient Clinic, Department of Child Health, Medical School, Univer-sity of Indonesia–Cipto Mangunkusumo Hospital in May 2002.Results Subjects were 57 homozygous β-thalassemic and 33 β-HbE-thalassemic patients. No one had regular desferoxamine orhistory of splenectomy. Proportions of increased ALT, TS, and posi-tive anti-HCV were 76%, 78%, and 6%, respectively. Duration ofillness, total volume of packed red cell (PRC) transfusions, TS level,and positive anti-HCV seemed to have role in the increased pro-portion of subjects with increased ALT, whereas duration of illnessand total volume of PRC seemed to have role in the increased TS.Conclusion Factors that seem to have a role in the increasedproportion of subjects who had increased ALT and TS were (1)duration of illness, total volume of PRC transfusion, TS, and posi-tive anti-HCV; 2) duration of illness and total volume of PRC trans-fusion, respectively